2017
DOI: 10.1002/adfm.201605928
|View full text |Cite
|
Sign up to set email alerts
|

Direct Synthesis of Large‐Scale WTe2 Thin Films with Low Thermal Conductivity

Abstract: 1 of 9) 1605928applications. [8][9][10][11][12][13][14] A spin quantum Hall state is also predicted in the distorted octahedral phase (1T′) of MX 2 in the monolayer limit, further extending applications of TMDs into spintronics and lowdissipation electronics. [13] As a part of the TMDs family, WTe 2 has recently attracted great interest due to its giant, nonsaturating magnetoresistance (MR) observed in bulk crystals, [15] and its predicted Weyl state. [16] Pressure-induced superconductivity and large spin-orbi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
103
0
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 98 publications
(112 citation statements)
references
References 45 publications
6
103
0
3
Order By: Relevance
“…Previous experiments have shown that the in-plane thermal conductivity is 15 ± 3 W m −1 K −1 for Td-WTe 2 flakes with thicknesses greater than 500 nm, [18] verifying our calculations. For bulk Td-WTe 2 , the calculated thermal conductivities along the a-, b-, and c-axis orientations are 14.93, 14.56, and 4.83 W m −1 K −1 , respectively.…”
Section: Doi: 101002/adma201804979supporting
confidence: 91%
See 3 more Smart Citations
“…Previous experiments have shown that the in-plane thermal conductivity is 15 ± 3 W m −1 K −1 for Td-WTe 2 flakes with thicknesses greater than 500 nm, [18] verifying our calculations. For bulk Td-WTe 2 , the calculated thermal conductivities along the a-, b-, and c-axis orientations are 14.93, 14.56, and 4.83 W m −1 K −1 , respectively.…”
Section: Doi: 101002/adma201804979supporting
confidence: 91%
“…To understand the role of these thermally active phonon modes, we calculate the in-plane cumulative thermal conductivity as a function of the phonon www.advmat.de www.advancedsciencenews.com frequency. [18] This isotropy can be attributed to comparable group velocities along the a-and b -axis orientations ( Figure S9, Supporting Information). Figure 4b presents the thin film lattice thermal conductivity of Td-WTe 2 computed for a 14 × 14 × 14 wavevector grid.…”
Section: Doi: 101002/adma201804979mentioning
confidence: 91%
See 2 more Smart Citations
“…The highly anisotropic thermal conductivity has also been observed in low‐symmetry TMDs such as T d WTe 2 , and ReS 2. Zhou et al reported the anisotropic thermal conductivity of WTe 2 flakes, where the thermal conductivity along the in‐plane is 15 times higher than along through‐plane.…”
Section: In‐plane Anisotropic Physical Propertiesmentioning
confidence: 92%